DETERMINANTS OF PHYSICAL FUNCTION IN COMMUNITY DWELLING OLD ADULTS. (11th November 2018) - Ramel, A; Geirsdottir, O; Chang, M; Jonsson, P; Thorsdottir, I
Abstract: Poor physical function is associated with adverse health outcomes in old adults. Several variables, e.g., nutrition, physical activity (PA), body composition, hematological variables, medication and cognitive function have been associated with physical function. However, findings from studies have been inconsistent and it is not known which are independent predictors of physical function. We conducted a cross-sectional study including 236 community dwelling old people (age range: 65–92 years, 58.2% female) in Reykjavik, Iceland. Timed-up-and-go (TUG), 6-minutes-wallk-for distance (6MWD), nutrition, PA, body composition, blood chemical variables, medication and cognitive function were assessed. We found bivariate correlations between physical function with body composition, strength, physical activity, number of medications, hematological variables, cognitive function, energy and protein intake. According to hierarchical linear models, body composition, strength, number of medications, PA and cognitive function were predictors of physical function but not hematological variables. Results were similar for both 6MWD and TUG and the strongest modifiable predictors in the final models were quadriceps strength/bodyweight (N/kg) ((+16.1m, P=0.001; -0.4sec, P=0.001), physical activity (h/week) (+2.2m, P=0.001; -0.04sec, P=0.021) and number of medications (-8.1m, P=0.003; +0.2sec, P=0.021). In community dwelling old adults, physical function decreases with age. However, there are modifiable determinants of physical function, in particular strength for a given body weight, PA and number of medications, which might give the possibility to maintain or improve physical function in this age group.